2012
DOI: 10.1021/cm2031812
|View full text |Cite
|
Sign up to set email alerts
|

Composition Control and Thermoelectric Properties of Quaternary Chalcogenide Nanocrystals: The Case of Stannite Cu2CdSnSe4

Abstract: A high-yield and upscalable colloidal synthesis route for the production of quaternary I 2 −II−IV−VI 4 nanocrystals, particularly stannite Cu 2+x Cd 1−x SnSe 4 , with narrow size distribution and precisely controlled composition is presented. It is also shown here how the diversity of valences in the constituent elements allows an effective control of their electrical conductivity through the adjustment of the cation ratios. At the same time, while the crystallographic complexity of quaternary chalcogenides is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 35 publications
3
82
0
Order By: Relevance
“…[21][22][23][24][25][26] Furthermore Zeier et al have shown that a restructuring process in the series of solid solutions Cu 2 Zn 1Àx Fe x GeSe 4 changes the c/2a axis ratio, which leads to enhanced point defect scattering and a reduction in the thermal conductivity due to the high local anisotropic structural disorder. 27 The changing bond angles and bond lengths in these materials strongly inuence the thermal transport properties in these materials.…”
Section: 14mentioning
confidence: 99%
“…[21][22][23][24][25][26] Furthermore Zeier et al have shown that a restructuring process in the series of solid solutions Cu 2 Zn 1Àx Fe x GeSe 4 changes the c/2a axis ratio, which leads to enhanced point defect scattering and a reduction in the thermal conductivity due to the high local anisotropic structural disorder. 27 The changing bond angles and bond lengths in these materials strongly inuence the thermal transport properties in these materials.…”
Section: 14mentioning
confidence: 99%
“…Other Method to Enhance ZT Bulk materials with complex structure (such as skutterudites [62], half-Heusler [63], Stannite [64], Zintl phases [65]) are promising approach to obtain high TE performance because of their intrinsic special structures [22]. Here, we can take skutterudite structure, for example.…”
Section: Methods To Enhance Ztmentioning
confidence: 99%
“…Indeed, for n-type PbS we showed dramatic improvements in ZT from 0.4 to 1.1 at 923 K by combining nanoprecipitates of Bi 2 S 3 and Sb 2 S 3 s phases with heavy PbCl 2 doping [58]. A comparison of some physical properties for optimized, highperformance n-and p-type Pb-based chalcogenide TE materials is listed in Table 10.2. At the same time, complex bulk materials [22] (such as skutterudites [62], half-Heusler [63], Stannite [64], Zintl phases [65]) have been explored and found that high efficiencies could indeed be obtained. Many of the recent high-ZTTE materials similarly achieve a reduced k lat through disordering the unit cell.…”
Section: Te Materialsmentioning
confidence: 99%
“…Because of the p-d hybridization of Cu3 d and Se4 p orbitals, the density of states (DOS) near the Fermi level would be localized. In this way, we would be able to improve the electrical conductivity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Although such investigations with respect to the hierarchical chemical bonds contributing to the low thermal conductivity are so far limited and are mostly focused on the cubic I-V-VI 2 semiconductors 15 and Nowotny–Juza compounds like α-MgAgSb with a non-caged structure 13 , we believe that this strategy is important for engineering the phonon transport of Cu-Sn-S compounds. In this regard, we specially substitute Se for S in the compound Cu 4 Sn 7.5 S 16 , aiming to engineer the band structure, phonon transport, and introduce lattice disorder, similar to the cases of Cu substitution for Cd 12 in Cu 2 CdSnSe 4 and Se for Te in n-type PbTe based solid solutions 17,18 .…”
Section: Introductionmentioning
confidence: 99%